Preliminary Rasch analysis of the multidimensional assessment of interoceptive awareness in adults with stroke. - Jena Blackwood; Sydney Carpentier; Wei Deng; Ann Van de Winckel (PLoS ONE, 2023)
Purpose The Multidimensional Assessment of Interoceptive Awareness (MAIA) measures interoceptive body awareness, which includes aspects such as attention regulation, self-regulation, and body listening. Our purpose was to perform a preliminary validation of the MAIA in adults with stroke using Rasch Measurement Theory. Methods The original MAIA has 32 items that measure interoceptive sensibility, which is an aspect of body awareness. We performed a preliminary analysis with Rasch Measurement Theory to evaluate the unidimensionality and structural validity of the scale. We investigated overall fit to assess unidimensionality, person and item fit, person separation reliability, targeting, local item dependence, and principal components analysis of residuals. Results Forty-one adults with chronic stroke (average 3.8 years post-stroke, 13 women, average age 57±13 years) participated in the study. Overall fit (χ 2 = 62.26, p = 0.26) and item fit were obtained after deleting 3 items and rescoring 26 items. One participant did not fit the model (2.44%). There were no floor (0.00%) or ceiling effects (0.00%). Local item dependence was found in 42 pairs. The person separation reliability was 0.91, and the person mean location was 0.06±1.12 logits. Conclusions The preliminary structural validity of the MAIA demonstrated good targeting and reliability, as well as unidimensionality, and good item and person fit in adults with chronic stroke. A study with a larger sample size is needed to validate our findings.